Reflexões arquivísticas no processo de gestão de documentos de imagens em movimento produzidos e/ou recolhidos em virtude da atividade fim de uma emissora de televisão - Aline de Queiroz Lopes (2016)
The work in the Documentation Center that stores documents of moving images, coming from a television station is the object of study of this research. The disquieting questions about how to improve the work in these spaces was the main motivation of the researcher, considering the importance of these collections, both to meet the demands of the institutions that produce them, as well as to the institutional memory and the whole society where the collection it's inserted. The empirical research methodology used, for data collection, an adaptation of participant observation in a Cedoc, as well as an interview with its manager. In addition, in two other collections of the same genre, interviews were also promoted and the routine and processes they performed were observed. We sought to discuss the actions carried out daily in these spaces, highlighting all the processes carried out through the selection, description, indexing and retrieval of the images. From the data obtained, we present a reflection about the actions performed in these spaces and the possible contributions of the archivology. It was verified that, in all investigated institutions, the name Cedoc is used, however, it was noticed that there is a need to revise this concept, considering the current situation of these collections. It was also found that there is a need to register the consensual policies that guide the work of these professionals, because the knowledge they use for decision making is only tacit knowledge. The study evidences the need of the professionals who work in these Cedocs to seek in the contributions of the archivology sources of information that allow to improve the work that has been developing.